2015
DOI: 10.1093/ejo/cjv032
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported pain after orthodontic treatments: a randomized controlled study on the effects of two follow-up procedures

Abstract: 182 Reg 2014, 16/09/2014 Comitato Etico Regione Liguria, Sez.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…A recent study conducted by Cozzani et al [ 36 ], shows that telephone follow-up after orthodontic treatment might be an effective procedure to reduce the pain threshold of patients. A question arose on whether to implement this procedure in a busy orthodontic practice or not.…”
Section: Literature Review/ Discussionmentioning
confidence: 99%
“…A recent study conducted by Cozzani et al [ 36 ], shows that telephone follow-up after orthodontic treatment might be an effective procedure to reduce the pain threshold of patients. A question arose on whether to implement this procedure in a busy orthodontic practice or not.…”
Section: Literature Review/ Discussionmentioning
confidence: 99%
“…A large body of evidence indicates that orthodontic pain can generate negative emotions (for example, anxiety) among orthodontic patients. 83 , 84 , 85 , 86 Moreover, negative emotions would in turn exacerbate orthodontic pain among orthodontic patients. 87 , 88 Thus, orthodontic pain and negative emotions are intertwined, and this connection could be explained by the role of limbic system.…”
Section: Neural Circuits and Regulation Of Orthodontic Painmentioning
confidence: 99%
“…112 These behavioural modalities share a common feature: reassurance and attention distraction. It has been well documented that orthodontic patients feel anxiety and stress following orthodontic pain, and an immediate follow-up could significantly reduce their orthodontic pain levels, 83 , 84 , 85 justifying that reassuring orthodontic patients may be a viable approach for controlling orthodontic pain. CBT, a form of psychotherapy, uses several treatment sessions to correct patients' negative altitudes and decrease their anxiety.…”
Section: Management Of Orthodontic Painmentioning
confidence: 99%
“…Regarding individual characteristics, the fact that women reported a greater impact of orthodontic pain is corroborated in the literature . This difference was attributed to the presence of sex hormones; however, this is speculative because these conditions were not evaluated.…”
Section: Discussionmentioning
confidence: 74%
“…Regarding age, some authors observed that adolescents report higher intensity and prevalence of pain after orthodontic appliance activation . Regarding sex, others have observed that women report higher mean pain scores . Patients’ socioeconomic stratum has also been considered to be relevant in the evaluation of pain .…”
Section: Introductionmentioning
confidence: 99%